2014
DOI: 10.1021/nn503753e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Interaction between Nitrogen-Doped Graphene and Porphyrin Molecules

Abstract: The chemical doping of graphene is a promising route to improve the performances of graphene-based devices through enhanced chemical reactivity, catalytic activity, or transport characteristics. Understanding the interaction of molecules with doped graphene at the atomic scale is therefore a leading challenge to be overcome for the development of graphene-based electronics and sensors. Here, we use scanning tunneling microscopy and spectroscopy to study the electronic interaction of pristine and nitrogen-doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 40 publications
7
75
0
Order By: Relevance
“…Color code for Dirac cone schemes: blue-empty states, red-filled states reported for porphyrin on N-doped graphene. 16 Our ab initio calculations indicate that, for E ¼ 0, a TCNQ molecules at a N-site gains 0.33 e, as compared to 0.20 e at C-sites. Although our calculations show that the interaction of TCNQ with graphene is increased by the nitrogen doping, the binding of TCNQ on Ndoped graphene is still of non-covalent nature (see supplementary information).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Color code for Dirac cone schemes: blue-empty states, red-filled states reported for porphyrin on N-doped graphene. 16 Our ab initio calculations indicate that, for E ¼ 0, a TCNQ molecules at a N-site gains 0.33 e, as compared to 0.20 e at C-sites. Although our calculations show that the interaction of TCNQ with graphene is increased by the nitrogen doping, the binding of TCNQ on Ndoped graphene is still of non-covalent nature (see supplementary information).…”
Section: Introductionmentioning
confidence: 72%
“…Recently, STM experiments have shown that molecules adsorbed at nitrogen sites exhibit a different electronic spectrum from those adsorbed on pristine areas, with a shifted or reduced electronic gap. [16][17][18] The effect of an applied electric field on these hybrid systems has however not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the doped-graphene exhibited the diverse potentials with physical and chemical characteristics in further improvement the unexploited and unexplored potential in graphene. Plasma doping Ultracapacitor Capacitance (280 F/g), novel cycle life (>200,000), and high-power capability [39] Pyrolysis Catalyst High O-reduction reaction [43] Thermal annealing in APCVD Organic molecular sensing Novel probing of Rhodamine (RhB) molecules [40] Thermal annealing in APCVD Ultrasensitive molecular sensor Novel sensing of RhB, crystal violet (CRV), and methylene blue (MB) molecules [41] Pyrolysis Catalyst High O-reduction reaction [37] Thermal annealing in CVD Fuel cells High O-reduction reactions, long-term stability, tolerance to crossover and poison [38] Plasma doping NA NA [42] Annealing at 1100 • C Back-gate FET Mobility (6000 cm 2 /Vs) [44] Plasma doping Biosensor High electrocatalytic activity, Novel glucose biosensing with low concentration (0.01 mM) [86] Electrothermal annealing FET Highly edge functionalization of GNRs by N 2 species [87] Wet chemical doping Catalyst Good electrocatalytic activity, long term stability, and tolerance to crossover effect [88] Soft thermal doping NA NA [92,94] Solvothermal doping Fuel cell Enhanced catalytic activity in O-reduction reaction [96] Thermal annealing in APCVD NA NA [95] Obviously, the TEM is an important technique to reveal the morphology, crystalline and chemical structures of nanomaterials. The information that TEM techniques can provide and their implications on applications is based on the assistances of low-magnification TEM, HR-TEM, spherical aberration-corrected HR-TEM, BF-TEM, DP-TEM, DF-TEM, STEM, DF-STEM, STEM_EELS, HAADF-STEM, and micro EDS-TEM.…”
Section: Applications Of Doped-graphenesmentioning
confidence: 99%
“…To attach macrocyclic molecules to graphene and GO, a broad spectrum of interactions can be employed, from amide or other covalent bonding to noncovalent (p-p stacking and van der Waals) and electrostatic interactions. 1,2,[4][5][6][8][9][10][11][12][13][14][15][16] The existence of carboxylic groups is an especially attractive property of GO, since it allows not only for the covalent functionalization through amide linkage with amino-substituted azamacrocycles, 1,2,4,10 but also offers the possibility of complexation between the oxygencontaining groups and coordinatively unsaturated central metal atoms of macrocyclic complexes. 17,18 Graphene and GO nanohybrids functionalized with tetraazamacrocyclic complexes possessing magnetic properties are materials of special interest, mainly from the point of view of organic spin electronic (or spintronic) devices.…”
Section: Introductionmentioning
confidence: 99%